Does IGFR1 inhibition result in increased muscle mass loss in patients undergoing treatment for pancreatic cancer?. Issue 4 (17th April 2014) - Fogelman, David R.; Holmes, Holly; Mohammed, Khalil; Katz, Matthew H. G.; Prado, Carla M.; Lieffers, Jessica; Garg, Naveen; Varadhachary, Gauri R.; Shroff, Rachna; Overman, Michael J.; Garrett, Christopher; Wolff, Robert A.; et al.
Abstract : Background: IGF‐1 plays a role in the growth of multiple tumor types, including pancreatic cancer. IGF‐1 also serves as a growth factor for muscle. The impact of therapeutic targeting of IGF‐1 on muscle mass is unknown. Methods: We evaluated muscle mass at L3 in patients enrolled in a randomized phase II study of MK‐0646 (M), a monoclonal antibody directed against the IGF‐1 protein, in patients with metastatic pancreatic cancer (MPC). Two different doses of M were tested, 5 and 10 mg/kg. We used the Slice‐o‐matic (ver 4.3) software to segregate CT images into muscle and fat components and measured muscle area (cm 2 ) at baseline and after 2 and 4 months of treatment. Patients received either gemcitabine with erlotinib (G + E), G + E + M, or G + M. Differences between the groups were compared using t tests. Results: Fifty‐three patients had both baseline and 2‐month imaging available for analysis. Of these, 42 received M with their chemo, and 11 had G + E only. After 2 months of treatment, both groups demonstrated decrease in muscle mass. G + E patients lost 5.6 % of muscle mass; M patients lost 9.1 and 8.6 % after treatment with 5 and 10 mg/kg, respectively ( p = 0.53). Patients demonstrating a response lost less muscle (median 4.6 %) than those with stable disease (9.6 %) and progressive disease (8.9 %, p = 0.14). Muscle retention from baseline to 2‐month imaging, defined as loss of <6 cm 2 of muscle, correlated with better survival than those patients demonstrating a muscle loss (HR 0.51, p = 0.03). Conclusions: MPC patients can be expected to lose muscle mass even while having clinical benefit (PR or SD) from chemotherapy. Muscle loss correlated with a risk of study drop‐out and death. There was a non‐significant trend toward greater muscle mass loss in patients on anti‐IGF‐1R therapy. However, it is unclear if this loss translates into functional differences between patients.